1998
DOI: 10.1007/s001470050441
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus genotypes and the influence of the induction of immunosuppression with anti-thymocyte globulin (ATG) on chronic hepatitis in renal graft recipients

Abstract: Hepatitis C virus (HCV) exhibits a dramatic genetic variability and several mechanisms of immunological response are unable to control hepatic and extrahepatic replication. Genotype 1 b is associated with more severe clinical manifestations and is less responsive to interferon. In addition, we have reported an increase of HCV RNA viral load after renal transplantation. Anti-thymocyte globulin (ATG) is supposed to increase viral replication and liver dysfunction in chronically infected renal graft recipients. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…We applied phylogenetic and phylodynamic analysis to NS5b sequences obtained from DAA naïve HCV infected patients to make the first characterization of the origin, diversity and epidemiologic history of HCV in Portugal. Like in previous studies, the most prevalent HCV variants were GT1a, representing almost half of the sequences analyzed, followed by GT3a and GT1b 58 – 62 . These genotypes are responsible for the majority of the HCV cases globally 63 , 65 , 66 .…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…We applied phylogenetic and phylodynamic analysis to NS5b sequences obtained from DAA naïve HCV infected patients to make the first characterization of the origin, diversity and epidemiologic history of HCV in Portugal. Like in previous studies, the most prevalent HCV variants were GT1a, representing almost half of the sequences analyzed, followed by GT3a and GT1b 58 – 62 . These genotypes are responsible for the majority of the HCV cases globally 63 , 65 , 66 .…”
Section: Discussionsupporting
confidence: 68%
“…Based on four previous studies performed between 1998 and 2014, the majority of HCV infections in Portugal are caused by GT1 followed by GT3, GT4 and GT2 58 63 . The origin, epidemiological history and transmission dynamics of these genotypes in Portugal have not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Another SRTR analysis observed similar patient survival in HCV+ recipients receiving depleting and nondepleting agents . In a retrospective review of 104 HCV‐infected kidney transplant recipients, patients who received induction with antithymocyte globulin had similar HCV viral load on follow‐up as compared to patients without induction . In a recent single‐center study that evaluated long‐term outcomes of 110 HCV‐infected patients after KTX, a subset analysis of 31 recipients showed that patients who received daclizumab had a worse progression of liver fibrosis score than patients receiving a lymphocyte‐depleting agent .…”
Section: Discussionmentioning
confidence: 95%
“…However, a major risk factor for infectious complications after solid organ transplantation is immunosuppression, including both maintenance therapy and agents used for induction or rejection. Some small studies have shown promising results with antithymocyte globulin or basiliximab in terms of viral infection, cirrhosis, and patient mortality in HCV+ renal transplant recipients . In a SRTR analysis, Luan et al .…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore avoided in HCVinfected patients after transplantation. On the other hand, the administration of the polyclonal antibody antithymocyte globulin (ATG) as induction therapy in 104 HCV-infected kidneytransplant patients did not induce viral replication [106], a finding that was confirmed by subsequent studies [107]. Contradictory data exist regarding monoclonal anti-IL2 antibodies, Advances in Treatment of Hepatitis C and B 236 Please use Adobe Acrobat Reader to read this book chapter for free.…”
Section: Induction Therapymentioning
confidence: 98%